Evaluation of Healthcare Professionals’ Knowledge on Code Blue: A Multi-Centre Survey Study: Healthcare Professionals’ Knowledge on Code Blue - Aslınur, Aslan (Journal Resuscitatio Balcanica, 2021)
Introduction: The Blue Code practice provides increase in survival rates and decrease in the rate of permanent sequelae after cardiac arrest. There are issues that healthcare workers should pay attention to in the Code Blue practice. Aim: The primary purpose of this survey study is to determine the knowledge levels of physicians and nurses about the Code Blue and cardiopulmonary resuscitation in 6 centres. The secondary aim is to determine the solutions that can be made to eliminate these deficiencies. Methods: After the approval of the Faculty Ethics Committee, Mersin University Faculty of Medicine, Adana Baskent Turgut Noyan Training and Research Hospital, Dokuz Eylül Univ. Faculty of Medicine, Hacettepe University Faculty of Medicine, Gulhane Training and Research Hospital, Manisa Celal Bayar Univ. Faculty of Medicine, except for the doctors and technicians of the Department of Anaesthesiology and Reanimation and the healthcare professionals working in the intensive care units, the doctors and nurses working in other departments were asked to answer the questions in the questionnaire via the internet with the questionnaire form stated in Appendix 1. Results: A total of 415 participants responded the survey. Of them, 45.8% were nurses, 24.8% residents, 23.3% faculty members, 5.4% specialist doctors and 0.7% general practitioners. Totally 86.6% of the participants knew the Code Blue number. To the question "What is the Code Blue?", 92.7% of the participants gave the correct answer to his question. "Do you hesitate to intervene when you encounter a patient requiring emergency intervention?" 25.9% of the participants answered "Yes" to the question. "Is there a form about Code Blue in your clinic?" 41% answered "No" to the question. Conclusion: According to the results of the survey we conducted, we are of the opinion that healthcare workers have insufficient knowledge about the Code Blue. In order to solve these problems, it would be appropriate to direct healthcare professionals to both in-hospital and external training programs.